Effect of temperature on the structure and magnetic properties of Co doped SiC films. (July 2017) - Sun, Xianke; Liu, Jiwen; Liu, Kuili; Wang, Shaohui; Zhao, Linlin; Qin, Wei; Wang, Gaoliang; Meng, Ming; Li, Jitao; Dong, Xue
Abstract: The Co-doped SiC films were developed by radio frequency-magnetron sputtering. After annealing at high temperatures, the amorphous structure of the films transformed into the structure of 3CSiC lattice and the secondary phase of the compounds CoSi. Some of the Co atoms began to occupy the C site of the SiC lattice in the form of Co 2+ ions with the annealing temperature rising above 600 °C, and formed the compounds CoSi entirely at 1200 °C. When the annealing temperature was below 800 °C, the saturation magnetization of the films increased with the increased annealing temperature. However, as the annealing temperature rose above 1000 °C, the saturation magnetization of the films decreased obviously. The formation of the compounds CoSi in the films restrained the magnetism derived from the doped Co atoms and some extended defects. Highlights: The Co-doped SiC films were developed by radio frequency-magnetron sputtering. All films were intrinsic ferromagnetism. Effect of annealing temperature on the magnetism of the films was studied. Formation of CoSi restrained magnetism derived from doped Co atoms and defects.